1979
DOI: 10.1002/jcp.1041010203
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of cytochalasin B and caffeine on control of DNA synthesis in normal and transformed cells

Abstract: Evidence is presented which suggests the existence of a t least two growth control points in cultured mammalian cells. These controls are in "parallel" rather than in "series." It is suggested that in normal and some transformed cells the controls are coupled while in SV40 transformed cells and tumor cells they are uncoupled. One control is revealed by cytochalasin B (CB) treatment since in normal and some kinds of transformed cells, CB treatment results in the accumulation or the arrest of cells in G1. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Caffeine has long been known to induce a G1 delay in mammalian cells [65][66][67], and we showed that caffeineinduced ~75% inhibition of G1/S progression in diploid human fibroblast strains. ATM and p53 were not required as AT cells and cells expressing HPV16E6 to inactivate p53 also arrested in G1 when incubated in caffeine.…”
Section: Discussionmentioning
confidence: 72%
“…Caffeine has long been known to induce a G1 delay in mammalian cells [65][66][67], and we showed that caffeineinduced ~75% inhibition of G1/S progression in diploid human fibroblast strains. ATM and p53 were not required as AT cells and cells expressing HPV16E6 to inactivate p53 also arrested in G1 when incubated in caffeine.…”
Section: Discussionmentioning
confidence: 72%
“…This means essentially normal segregation of chromosomes and filial nucleus formation. Therefore, treatment of the cells with CD results in formation of multinuclear cells in culture [26, 29, 30]. In our recent study we have shown that spontaneously derived or colcemid‐induced micronuclei cause activation of p53 with strong dependence on their number [31].…”
Section: Discussionmentioning
confidence: 99%
“…This relatively high daily consumption, as well as the abundance of methylxanthines (primarily caffeine) in dietary substances, has stimulated extensive research into the question of methylxanthine toxicity particularly with respect to coronary heart disease and cancer (Bertrand et al, 1970;Jick et al, 1973;Mann and Thorogood, 1975;Rall, 1980;Curatolo and Robertson, 1983;Dews et al, 1984;Pozniak, 1985). Caffeine has been shown to inhibit enzymes required for DNA synthesis, cause an increase in chromatin condensation, increase the length of the GI phase, and exhibit antimutagenic activity against N-methyl-N'-nitro-N-nitrosoguanidine (Borodina et al, 1979;O'Neal, 1979;Levin, 1982;Roberts, 1984;Kunicka et al, 1990;Selby and Sancar, 1990). In the presence of DNA-modifying agents, high concentrations of caffeine (>10 mM) appear to enhance cell mortality (Roberts, 1984).…”
Section: Introductionmentioning
confidence: 99%